2016
DOI: 10.1371/journal.pone.0147791
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Mealworm Protein for Food Purposes - Extraction and Functional Properties

Abstract: A protocol for extraction of yellow mealworm larvae proteins was established, conditions were evaluated and the resulting protein extract was characterised. The freeze-dried yellow mealworm larvae contained around 33% fat, 51% crude protein and 43% true protein on a dry matter basis. The true protein content of the protein extract was about 75%, with an extraction rate of 70% under optimised extraction conditions using 0.25 M NaOH, a NaOH solution:ethanol defatted worm ratio of 15:1 mL/g, 40°C for 1 h and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
182
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(212 citation statements)
references
References 30 publications
(58 reference statements)
24
182
4
2
Order By: Relevance
“…Consequently, the crude fat content of the un‐defatted and defatted meal were found to be 32.09 ± 0.59% and 1.05 ± 0.07%, respectively (Table ). The fat constituent of the un‐defatted meal was consistent with what has been reported by Barragan‐Fonseca et al (), but was found to be a little lower than what has been indicated for other insect larvae like the yellow mealworm—33% (Zhao et al, ) and 35% (Jones, Cooper, & Harding, ). Thus, in terms of fat composition, HIL may be an option or equal preference to other insect species.…”
Section: Resultssupporting
confidence: 89%
“…Consequently, the crude fat content of the un‐defatted and defatted meal were found to be 32.09 ± 0.59% and 1.05 ± 0.07%, respectively (Table ). The fat constituent of the un‐defatted meal was consistent with what has been reported by Barragan‐Fonseca et al (), but was found to be a little lower than what has been indicated for other insect larvae like the yellow mealworm—33% (Zhao et al, ) and 35% (Jones, Cooper, & Harding, ). Thus, in terms of fat composition, HIL may be an option or equal preference to other insect species.…”
Section: Resultssupporting
confidence: 89%
“…The former is lower than other mealworm protein contents in the literature Zhao, Vázquez-Gutiérrez, Johansson, Landberg, and Langton (2016). Protein content (dry weight basis) of NC and CP, determined by BCA method, was 59.8% and 76.9%, respectively.…”
mentioning
confidence: 64%
“…FAC is closely related to the protein content and is also affected by some factors like source of protein, processing conditions, composition of additive, size of particles, and temperature (Zayas, ). The aggregate formation and exposed hydrophobic amino acids may be responsible for varied FAC of proteins (Zhao, Vazquez‐Gutierrez, Johansson, Landberg, & Langton, ). Foh et al () also reported 2.43 ml/g of OHC of FMMC.…”
Section: Resultsmentioning
confidence: 99%